2017
DOI: 10.1016/j.bbadis.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles derived from obese adipose tissue elicit a pro-inflammatory phenotype of CD16 + , CCR5 + and TLR8 + monocytes

Abstract: Macrophage infiltration into adipose tissue (AT) is a hallmark of the chronic inflammatory response in obesity and is supported by an intense monocyte migration towards AT. Although it has been detected an increased proportion of circulating CD16 monocyte subsets in obese subjects, the mechanisms underlying this effect and the contribution of these cells to the inflamed profile of obese AT are still poorly understood. We investigated whether factors secreted by human obese omental AT could polarize monocytes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 70 publications
1
26
0
Order By: Relevance
“…A similar phenomenon has been reported involving microparticles, HIV, and CXCR4 (Rozmyslowicz et al, 2003). CCR5 expression is also influenced by the release of EVs, specifically microparticles (Renovato-Martins et al, 2017). Therefore, EVs have the potential to attribute greater complexity to CCR5 roles in viral infections.…”
supporting
confidence: 68%
“…A similar phenomenon has been reported involving microparticles, HIV, and CXCR4 (Rozmyslowicz et al, 2003). CCR5 expression is also influenced by the release of EVs, specifically microparticles (Renovato-Martins et al, 2017). Therefore, EVs have the potential to attribute greater complexity to CCR5 roles in viral infections.…”
supporting
confidence: 68%
“…An increased proportion of circulating CD16 þ monocyte subsets is found in obese subjects, although the mechanisms underlying this effect and the contribution of these cells to the inflammatory state are unknown. Renovato-Martins et al 40 showed that explants of human obese omental adipose tissue, obtained during bariatric surgery, released higher levels of macrophage inflammatory protein 1-α (MIP1-α), tumor necrosis factor-α (TNF-α), leptin, and also vascular endothelial growth factor (VEGF), together with increasing amounts of MPs, when compared with explants of lean subcutaneous adipose tissue. Conditioned media or MPs released from obese omental adipocytes increased CD16 and CCR5 expression on CD14 þ CD16 À monocytes and augmented their migratory capacity toward the conditioned media from obese omental adipose tissue, itself, but was inhibited when MIP1-α was neutralized.…”
Section: Tissue Factor and Monocyte/macrophages And Microparticlesmentioning
confidence: 99%
“…Renovato-Martins et al demonstrate that monocyte infiltration into adipose tissue is a signature of organ early development, while macrophage infiltration is a hallmark of the inflammatory response in the adipose tissues of obesity patients [48]. Similarly, Wolf 's group found that the feedback loop between monocytes and macrophages not only provides immunological defense but also contributes to maintaining the function of EAT, which involves thermogenesis, metabolic balance, and local sympathetic nerve distribution [49].…”
Section: Discussionmentioning
confidence: 99%